Jumbuy!: Preloved e-mall web-based system - Cassandra Christine Charlseak (2022)
Business-to-consumer (B2C) marketing is a method of selling products and services immediately between a company and consumers who are the end-users of the company's products or services. Most businesses that sell directly to consumers are classified as B2C. An online system platform such as e-commerce system allowing users to buy product whether it is new or preloved items on the internet. There are a lot of platforms that develop to sell preloved items. There are many e-commerce platforms that are already developed such as Carousell. This has become a lot of competition that always been a problem to develop an e-commerce application. Some students cannot afford to buy a new edition of reference books. Mostly, the new edition or new released books are quite expensive and some of the reference books can be found in the library but are limited and there is specific amount of time on how long student can borrow the books. It is better to shop online as the user as they can just simply relax at their home while finding the item that they desired at the best price as they can compare it to another seller. The purpose of developing this project is to let students in Universiti Malaysia Sabah to buy preloved items. This report will be describing about the e-commerce system that will be develop called JumBuy!: Preloved e-mall web-based system. JumBuy!: Preloved e-mall system is an e-commerce web-based system that helps student to buy items such as preloved books, so that another student can buy with affordable price.